The Influence of High-Stakes Accountability Policy on Teacher Job Satisfaction and Turnover - Curtiss, Caroline (East Carolina University, 2015)
The current study examined the impact of teacher stress related to high-stakes testing and educational policy changes on teacher turnover. Predictors of teacher turnover such as demographics, stress, educational policy changes, commitment to organization, and school climate were examined in this online survey study. Job satisfaction was examined as a mediator of teacher turnover intent. The theory guiding this study was the Theory of Planned Behavior (Ajzen, 1991), which states that turnover intent is the closest action to actual turnover. A total of 5,000 teachers from North Carolina were invited to participate in an online survey. Five hundred and thirteen teachers completed the survey. Correlational, regression, and structural equation modeling analyses revealed a significant relationship between teacher stress and teacher turnover as well as significant relationships between educational policy changes and teacher turnover. Commitment to organization also revealed a significant relationship, while school climate yielded a significant relationship in regression analysis only. This study is limited to North Carolina and future research should examine longitudinal studies across multiple states. Implications for educational policy are discussed.
Keywords: Psychology; Educational psychology; Educational policy; High-stakes testing; Stress; Turnover; Educational accountability--North Carolina; Education and state--North Carolina; Teachers--Job stress--North Carolina; Teacher turnover--North Carolina; Teachers--Job satisfaction--North Carolina